The seamstress of sardinia eaudiobook A novel. - Pitzorno, Bianca (HarperAudio, 2022)
A bestselling Italian writer makes her American debut with this delightful dramedy of manners, family, romance, and fashion that is set on the island of Sardinia at the end of the nineteenth century—a dazzling and original literary blend of Jane Austen and Adriana Trigiani. In 1900 Sardinia, a young woman's remarkable talent with a needle earns her a position as a seamstress with a wealthy family. Inside this privileged world far different from her own humble beginnings, the skilled sewer quietly takes measurements, sketches designs, mends hems—and in the silence, hears whispered secrets and stories of all those around her. Through the watchful young seamstress's eyes, this small Italian city and its residents emerge in all their vitality, vanity, and fragility—flawed yet congenial people who are not quite what they pretend to be. There is the Marchesa Esther, who rides horses and studies mechanics and ancient Greek; Miss Lily Rose, a spirited American journalist who commissions a special corset—with pockets to hide more than just her flaws; the Provera sisters with their expensive Parisian fashions that belie their financial hardships; and Assuntina, the wild child. There are men, young, old, and in between; love affairs and broken hearts; and even a murder (or was it suicide?). And at the center, watching and waiting is the seamstress herself, an intelligent, ambitious girl with a tender heart and her own impossible dream. An irresistible literary confection rich in atmosphere and period detail and packed with compelling characters. The Seamstress of Sardinia transports us to a long-ago world not so removed from our own—to a society rigidly divided by wealth and shaped by passion, hope, ambition, and love—the elemental forces that drive human lives.